Analisa Sikap dan Perilaku Nasabah terhadap Produk Simpeda pada PT Bank Kalbar Cabang Mempawah - Harry Setiawan; Rafles Ginting (Jurusan Akuntansi Politeknik Negeri Pontianak, 2021)
Kalbar Bank branch of Mempawah places the product position by establishing the attributes of product and profenent facility which expected to give influence to the customers decision on determining their choice on a product as its market strategy. The research on it bears attribute of achievable office location as the most interesting attribute. While the small minimum deposit becomes the most uninteresting attribute on costumer perception. Generally, the costumers expect for the friendly servicing from the bank official and the most establishing factor of costumers choice on Simpeda product is the credibility of Kalbar Bank as the trusted bank in public. The attitude is a stimulus which may attrack the costumers to buy a product. The expected attitude is surely the positif one, which depends on the attributes that belong to the products and also other proponent factors. The study through the attributes shows that all the costumers or respondents still trust on Simpeda of Kalbar Bank as their saving choice because the lack on one attribute may be compensated by the superiority of others. We may have as a conclusion that the costumers or respondents attitude of Simpeda of Kalbar Bank is categorized in good one.